Sex differences in volume overload in skinned fibers. Issue 1 (December 2016) - Bening, C.; Hamouda, K.; Leyh, R.
Abstract Background The impact of sex on cardiac morphology and function in chronic volume overload has been described in detail. However, the relation between sex and contractile properties at the actin-myosin level has not been well defined. Therefore, we evaluated the influence of sex on the contractile capacities of patients with chronic volume overload. Methods In 36 patients (18 males, 65 ± 9 years; 18 females, 65 ± 13 years) scheduled for elective mitral valve surgery due to severe mitral regurgitation (MR) with preserved left ventricular function, right auricle samples were obtained prior to extracorporal circulation. The fibers were prepared and skinned and exposed to a gradual increase in the calcium concentration (from pCa of 6.5–4.0) for calcium-induced force-developing measurements. Calcium sensitivity was also measured and recorded. Results The pCa-force relationship of the fibers obtained from males and females was significantly different, with the force values of the female fibers greater than those of male fibers at maximum calcium concentrations (pCa of 4.0: 3.6 ± 0.3 mN versus 3.2 ± 0.4 mN, p 0.02) and pCa of 4.5 2.6 ± 0.6 versus 2.0 ± 0.5, p 0.002). In contrast, the force values of female fibers were lower at mean calcium concentrations compared to those of male fibers (at 5.5 and pCa of 6.0: 1.0 ± 0.3 mN versus 1.2 ± 0.5 mN, p 0.04; 0.61 ± 0.05 versus 0.88 ± 0.09, p 0.04). Calcium sensitivity was observed at pCa of 5.0 in females and pCa of 4.5 in males. Conclusion This study demonstrated that female fibers from patients exposed to chronic volume overload developed higher force values at a given calcium concentration compared to fibers from male patients. We assume that female patients might tap the full force potential, which is required when exposed to the highest calcium concentrations in our experimental cycle. The calcium sensitivity among genders was significantly different, with the results suggesting that males have higher calcium sensitivity and might compensate for lower force values at maximal calcium concentrations by a higher affinity for calcium. Hence, female patients with MR seem to work more "energy efficient".